An Interprofessional Curriculum on Antimicrobial Stewardship Improves Knowledge and Attitudes Toward Appropriate Antimicrobial Use and Collaboration. (31st January 2017) - MacDougall, Conan; Schwartz, Brian S.; Kim, Lisa; Nanamori, Mari; Shekarchian, Sharmin; Chin-Hong, Peter V.
Abstract: Background: Inappropriate antimicrobial use can threaten patient safety and is the focus of collaborative physician and pharmacist antimicrobial stewardship teams. However, antimicrobial stewardship is not comprehensively taught in medical or pharmacy school curricula. Addressing this deficiency can teach an important concept as well as model interprofessional healthcare. Methods: We created an antimicrobial stewardship curriculum consisting of an online learning module and workshop session that combined medical and pharmacy students, with faculty from both professions. Learners worked through interactive, branched-logic clinical cases relating to appropriate antimicrobial use. We surveyed participants before and after the curriculum using validated questions to assess knowledge and attitudes regarding antimicrobial stewardship and interprofessional collaboration. Results were analyzed using paired χ 2 and t tests and mixed-effects logistic regression. Results: Analysis was performed with the 745 students (425 medical students, 320 pharmacy students) who completed both pre- and postcurriculum surveys over 3 years. After completing the curriculum, significantly more students perceived that they were able to describe the role of each profession in appropriate antimicrobial use (34% vs 82%, P < .001), communicate in a manner that engaged the interprofessional team (75% vs 94%, P < .001), and describe collaborative approaches to appropriate antimicrobial use (49% vs 92%, P < .001). Student favorability ratings were high for the online learning module (85%) and small group workshop (93%). Conclusions: A curriculum on antimicrobial stewardship consisting of independent learning and an interprofessional workshop significantly increased knowledge and attitudes towards collaborative antimicrobial stewardship among preclinical medical and pharmacy students.